Wheel Bearings with a Long Maintenance Interval as a Response to Extending Wheel Life (Current Problems in Rail Vehicles, 2021)
Railway bearings and wheels are very important components of a railway vehicle that is subject to relatively rapid wear, which requires maintenance. The operators of rolling stock focus on the reduction of maintenance cost and call for extending of maintenance interval. The extension of maintenance interval reduces the service cost but in other hand it creates the risk of bearing damage and wheel wear. This trend increases requirements on the wheel material and also on the complete bearing arrangement. The internal design of bearing must be modified and online condition monitoring of bearing behaviour during train operation isrequired as well. The paper is focusing on the importance of bearing and wheel maintenance planning and their harmonization.
Keywords: wheel bearing; railway wheel; maintenance interval; online condition monitoring